Clinical significance of cytogenetic and molecular genetic abnormalities in 634 Chinese patients with myelodysplastic syndromes. (20th February 2021) - Yan, Xuefen; Wang, Lu; Jiang, Lingxu; Luo, Yingwan; Lin, Peipei; Yang, Wenli; Ren, Yanling; Ma, Liya; Zhou, Xinping; Mei, Chen; Ye, Li; Xu, Gaixiang; et al.
Abstract: Purpose: To explore the relevance of cytogenetic or molecular genetic abnormalities to clinical variables, including clinical and laboratory characteristics and prognosis in Chinese patients with myelodysplastic syndromes (MDS). Methods: A total of 634 consecutive patients diagnosed with MDS at The First Affiliated Hospital, Zhejiang University School of Medicine from June 2008 to May 2018 were retrospectively included in this study. All patients had evaluable cytogenetic analysis, and 425 patients had MDS‐related mutations sequencing. Results: 38.6% of patients displayed abnormal karyotypes. The most common cytogenetic abnormality was +8 (31%). Sole +8 was related to female ( p = 0.002), hemoglobin >10 g/dL ( p = 0.03), and <60 years old ( p = 0.046). TP53 mutations were associated with complex karyotype (CK) ( p < 0.001). DNMT3A mutations correlated with ‐Y ( p = 0.01) whereas NRAS mutations correlated with 20q‐ ( p = 0.04). The overall survival (OS) was significantly inferior in patients with +8 compared with those with normal karyotype (NK) ( p = 0.003). However, the OS of sole +8 and +8 with one additional karyotypic abnormality was not different from NK ( p = 0.16), but +8 with two or more abnormalities had a significantly shorter OS than +8 and +8 with one additional karyotypic abnormality ( p = 0.02). In multivariable analysis, ≥60 years old, marrow blasts ≥5% and TP53 mutations were independent predictors for poor OS ( p < 0.05), whereas SF3B1 mutations indicated better prognosis. Male IDH1 and IDH2 mutations and marrow blasts ≥5% were independent risk factors for worse leukemia free survival (LFS) ( p < 0.05). Conclusion: In this population of Chinese patients, trisomy 8 is the most common karyotypic abnormality. Patients with +8 showed a poorer OS compared with patients with NK. Sole +8 and +8 with one additional karyotypic abnormality had similar OS with NK, whereas +8 with two or more abnormalities had a significantly shorter OS. DNMT3A mutations correlated with ‐Y and NRAS mutations correlated with 20q‐. TP53 mutations were associated with CK and had a poor OS. SF3B1 mutations indicated a favorable OS. IDH1 and IDH2 mutations independently indicated inferior LFS. Abstract : This study aimed to explore the relevance of cytogenetic or molecular genetic abnormalities to clinical variables, including clinical and laboratory characteristics and prognosis in patients with myelodysplastic syndromes (MDS) and showed that cytogenetic changes had a potential correlation with molecular genetic abnormalities and both had significant influence on the prognosis of MDS.